Optimization of Biodiesel Synthesis Process from Waste Cooking Oil in a Phased Array Ultrasonic Reactor Using Response Surface Methode - Priscilla, Tiara; Ardycha Yudha Ramadhani, Muhammad; Prayogo, Wempi; Nurjannah, Nikmah; Achmad Parmadi, Faris; Arifin, Zainal (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2023)
The research aims to optimize the process of biodiesel synthesis from used cooking oil using Response Surface Methodology (RSM) in ultrasonic phased array reactor. Used cooking oil, as a potential waste source, has been identified as a sustainable alternative feedstock for biodiesel production. The use of ultrasonic phased array reactors is expected to improve conversion efficiency through cavitation to produce high yields and purity of biodiesel. RSM used to obtain the optimal combination of transesterification reaction conditions, including variables such as feedstock ratio, catalyst concentration, and reaction time. A quantity of methanol and NaOH was transesterified in a reactor that had been filled with used cooking oil. The results showed the yield of biodiesel was achieved at 90.3250% with an optimum mole ratio of 1:7.59 (oil to methanol), a catalytic concentration of NaOH 0.14% by weight of oil and a reaction time of 15 minutes. The oil/methanol ratio is the most important operating parameter based on the ANOVA test. Based on the physical properties of biodiesel on density, kinematic viscosity, flash point, carbon residue and based on the results of GC-MS testing the biodiesel produced is in accordance with SNI 7182:2015.